Characterising the ambient sound environment for infants in intensive care wards. (6th April 2016) - Shoemark, Helen; Harcourt, Edward; Arnup, Sarah J; Hunt, Rod W
Abstract : Aim: The purpose of this study is to characterise ambient sound levels of paediatric and neonatal intensive care units in an old and new hospital according to current standards. Methods: The sound environment was surveyed for 24‐h data collection periods ( n = 80) in the Neonatal and Paediatric Intensive Care Units (NICUs and PICUs) and Special Care Nursery of the old and new Royal Children's Hospital Melbourne. The ambient sound environment was characterised as the proportion of time the ongoing ambient sound met standard benchmarks, the mean 5‐s sound levels and the number and duration of noise events. Results: In the old hospital, none of the data collection periods in the NICU and PICU met the standard benchmark for ongoing ambient sound, while only 5 of the 22 data collection periods in the new hospital met the recommended level. There was no change in proportion of time at recommended Leq between the old and the new Special Care Nursery. There was strong evidence for a difference in the mean number of events >65 dBA (Lmax ) in the old and new hospital (rate ratio = 0.82, 95% confidence interval: 0.73 to 0.92, P = 0.001). The NICU and PICU were above 50 dBA in 75% of all data collection periods, with ventilatory equipment associated with higher ongoing ambient sound levels. Conclusions: The ongoing ambient sound suggests that the background sound environment of the new hospital is not different to the old hospital. However, there may be a reduction in the number of noise events.